B''/PR72 subunit mediates Ca²⁺-dependent dephosphorylation of DARPP-32 by protein phosphatase 2A - Ahn, Jung-Hyuck; Sung, Jee Young; McAvoy, Thomas; Nishi, Akinori; Janssens, Veerle; Goris, Jozef; Greengard, Paul; Nairn, Angus C (Proceedings of the National Academy of Sciences - PNAS, 2007)
In dopaminoceptive neurons, dopamine- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32) plays a central role in integrating the effects of dopamine and other neurotransmitters. Phosphorylation of DARPP-32 at Thr-34 by protein kinase A results in inhibition of protein phosphatase 1 (PP1), and phosphorylation at Thr-75 by Cdk5 (cyclin-dependent kinase 5) results in inhibition of protein kinase A. Dephosphorylation at Thr-34 involves primarily the Ca²⁺-dependent protein phosphatase, PP2B (calcineurin), whereas dephosphorylation of Thr-75 involves primarily PP2A, the latter being subject to control by both cAMP- and Ca²⁺-dependent regulatory mechanisms. In the present study, we have investigated the mechanism of Ca²⁺-dependent regulation of Thr-75 by PP2A. We show that the PR72 (or B'' or PPP2R3A) regulatory subunit of PP2A is highly expressed in striatum. Through the use of overexpression and down-regulation by using RNAi, we show that PP2A, in a heterotrimeric complex with the PR72 subunit, mediates Ca²⁺-dependent dephosphorylation at Thr-75 of DARPP-32. The PR72 subunit contains two Ca²⁺ binding sites formed by E and F helices (EF-hands 1 and 2), and we show that the former is necessary for the ability of PP2A activity to be regulated by Ca²⁺, both in vitro and in vivo. Our studies also indicate that the PR72-containing form of PP2A is necessary for the ability of glutamate acting at α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid and NMDA receptors to regulate Thr-75 dephosphorylation. These studies further our understanding of the complex signal transduction pathways that regulate DARPP-32. In addition, our studies reveal an alternative intracellular mechanism whereby Ca²⁺ can activate serine/threonine phosphatase activity.